EFFECTS OF HYDROCARBON POLLUTED SOIL ON THE BIOMASS AND PROTEIN CONTENT OF COWPEA AND MAIZE SEEDLINGS - Achuba, F. I. (The Faculty of Agriculture Obafemi Awolowo University, Ile-Ife, Nigeria., 2018)
Effect of hydrocarbon from crude oil released into the environment, including farmlands on production continues to cause both physical and metabolic derangements in crops. The objective of this study was to determine the effect of hydrocarbon tainted soil on the biomass and levels of protein in both cowpea (Vigna unguiculata L Walp) and maize ( Zea mays L) seedlings. The soil was treated with hydrocarbons (kerosene, diesel, engine oil and petrol) at different concentrations (0.0% 0.1%, 0.25%, 0.5%, 1.0% and 2.0% (v/w). The experimental set up was completely randomized design and treatment was replicated five times. Three seeds were planted in each bag and watered daily. The biomass of the whole seedling and  protein content were determine  on each crop stating from four  days after germination at interval of four days. The results revealed that the hydrocarbons caused significant (P<0.01) decrease in the biomass as well as the protein content in both cowpea and maize seedlings. The hydrocarbons exhibited differential effects on the biomass and the levels of protein in the crop seedlings. It is obvious that hydrocarbons toxicity is dependent on the type of product as well as crop under consideration